2021
DOI: 10.3389/fpsyg.2021.671817
|View full text |Cite
|
Sign up to set email alerts
|

The Developing Brain in the Digital Era: A Scoping Review of Structural and Functional Correlates of Screen Time in Adolescence

Abstract: The widespread diffusion of screen-based devices in adolescence has fueled a debate about the beneficial and detrimental effects on adolescents’ well-being and development. With the aim of summarizing the existing literature on the associations between screen time (including Internet-related addictions) and adolescent brain development, the present scoping review summarized evidence from 16 task-unrelated and task-related neuroimaging studies, published between 2010 and 2020. Results highlight three important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 124 publications
1
25
0
2
Order By: Relevance
“…In particular, during home quarantine, social media use was the only way to meet and socialize, thus contributing to longer time spent online and more frequently reported symptoms of social media addiction, especially when adolescents experienced FoMO, thus diminishing well-being ( 64 ) - in particular, FoMO proneness was higher at the early stage of the pandemic ( 64 ). Given that adolescents' self-control skills are still underdeveloped due to the immaturity of the prefrontal cortex, younger age groups were even more at risk of developing symptoms of media addiction during the pandemic, which was further facilitated by the instantaneous and easy-to-access gratifying contents that (social) media platforms convey ( 65 , 71 ). According to the Interaction of Person-Affect-Cognition-Execution Model ( 72 ), the experience of psychological distress, such as the one created by the Covid-19 lockdown, likely contributed to the development of addictive Internet use.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, during home quarantine, social media use was the only way to meet and socialize, thus contributing to longer time spent online and more frequently reported symptoms of social media addiction, especially when adolescents experienced FoMO, thus diminishing well-being ( 64 ) - in particular, FoMO proneness was higher at the early stage of the pandemic ( 64 ). Given that adolescents' self-control skills are still underdeveloped due to the immaturity of the prefrontal cortex, younger age groups were even more at risk of developing symptoms of media addiction during the pandemic, which was further facilitated by the instantaneous and easy-to-access gratifying contents that (social) media platforms convey ( 65 , 71 ). According to the Interaction of Person-Affect-Cognition-Execution Model ( 72 ), the experience of psychological distress, such as the one created by the Covid-19 lockdown, likely contributed to the development of addictive Internet use.…”
Section: Discussionmentioning
confidence: 99%
“…Screen-based media use (including Internet-related addictive behaviors) is associated with a less efficient cognitive control system in adolescence. Adolescents with IGD more frequently exhibit decreased short- and medium-range connectivity among the subcortical, frontal, and parietal regions involved in attentional and control networks, in line with other behavioral addictions [ 57 , 58 , 59 ]. IGD is linked to functional and structural neural changes in the fronto-striatal and fronto-cingulate regions [ 43 ].…”
Section: What Is Game Addiction?mentioning
confidence: 99%
“…Fronto-striatal dysfunction is also thought to promote a compulsive use of the Internet and screen devices in general. It has been reported that adolescents who play action video games more frequently struggle to maintain their attention over time [ 58 ]. Adolescents typically exhibit more reward anticipation brain activity than adults do.…”
Section: What Is Game Addiction?mentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of their developmental period, there is reduced connectivity between cognitive control and subcortical structures involved in reward processing in young populations (Marciano et al, 2021). Previous evidence did not find a difference between problematic social media use between younger adolescents and young adults, however psychopathological risk for the development of problematic use did differ between ages (Cerniglia et al, 2019).…”
Section: Social Media Use and The Developing Brainmentioning
confidence: 91%